Increased Urine Interleukin-17 and Interleukin-22 Levels in Patients With Candidal Urinary Tract Infection (Iranian Journal of Kidney Diseases, 2018)
Introduction. Candiduria is common in the hospitalized patients. This study aimed to quantify interleukin (IL)-17 and IL-22 levels in urine of candiduric patients. Materials and Methods. A case-control study was conducted on inpatients at Hashemi Nejad Kidney Center. Thirty-four patients were identified with Candida species in their urine samples (> 103 colony-forming units per milliliter and presence of Candida species only). Urine samples with concomitant infections were excluded. Thirty-four patients with negative direct examination and culture were included as the control patients. Interleulin-17 and IL-22 levels were measured in the lyophilized and nonlyophilized urine. The relevant cytokine titers of the two groups were compared, and the association of cytokine elevation and candiduria was investigated. Results. The majority of the candiduric patients were from the intensive care and urology units of women. Only 4 patients (11.7%) manifested fever and dysuria. Massive leukocyturia was observed in 4 patients. Candida glabrata was the most commonly isolated species (44%). Levels of the urine IL-17 and IL-22 were significantly elevated in the candiduric patients, when compared to the noncandiduric controls. While an increased IL-17 level was significantly associated with candiduria (odds ratio, 1.09; 95% confidence interval, 1.003 to 1.17; P = .04), an increased IL-22 level was not. The results showed that lyophilized urine samples maximized the detection power of urinary cytokines. Conclusions. Our results indicated that direct examination, fungal urine culture, and investigation of urine IL-17 and IL-22 levels are useful tools for diagnosis of Candida urinary tract infection.